Penentuan Harga Beli Opsi Asia Menggunakan Monte Carlo-Antithetic Variate dan Monte Carlo-Control - Fahrezal Zubedi; Novianita Achmad; Sri Lestari Mahmud; Rusli Mowuu (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
Math is applicable in many fields, including financial computing and discussing options. Options are contracts between two parties. The first part acts as a buyer with non-obligatory rights to buy or sell from the second party, who act as the seller with particular assets of predetermined time and price. This research aims to compare the monte Carlo-Antithetic Variate and monte Carlo-Control Variate in determining the purchase price of the Asian option. This study uses data from the closing price of the daily stock of PT Adhi Karya Tbk from October 1st, 2018 – to November 27th, 2019. The findings revealed varying option prices and different error standards. The Antithetic Variate simulation produces option price Rp. 246,6821 and error standard 0,071495 in 10000000th simulation and the Control Variate simulation produce option price Rp. 183,2139 and error standard 0,09716 in the 5000th simulation.  The result was that the Control Variate was considered better at determining Asian option purchase price because of the smaller option and faster error standard in approaching zero.